Q: What is 7a 4 as the exponent times 3a 2 as the exponent?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

4a - 5 = 7a - 7 -5 = 3a - 7 2 = 3a a = 3/2

The answer to the expression 25a^5 + 15a^4 - 35a^3 - 40a^3 + 10a divided by 5a is 5a^4 + 3a^3 - 7a^2 - 8a + 2.

4a-2=7a-6 4=3a a=4/3

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2

Related questions

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

4a - 5 = 7a - 7 -5 = 3a - 7 2 = 3a a = 3/2

The answer to the expression 25a^5 + 15a^4 - 35a^3 - 40a^3 + 10a divided by 5a is 5a^4 + 3a^3 - 7a^2 - 8a + 2.

Clearly, there are some signs missing. So let's try the four possibilities for the second terms: 1. + and + 3a + 4b = 7a + 4b Subtract 4b from each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 2. + and - 3a + 4b = 7a - 4b Subtract 4b from each side: 3a = 7a - 8b Subtract 7a from each side: -4a = -8b or 4a = 8b Answer: a = 2b 3. - and - 3a - 4b = 7a - 4b Add 4b to each side: 3a = 7a Subtract 3a from each side: 0 = 4a Answer : a = 0, b indeterminate (ie can have any vaue). 4. - and + 3a - 4b = 7a + 4b Add 4b to each side: 3a = 7a + 8b Subtract 7a from each side: -4a = 8b or 4a = -8b Answer: a = -2b Can't do better than that with the information available.

4a-2=7a-6 4=3a a=4/3

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2

7a + 10 = 2a 7a = 2a -10 5a = -10 a = -2

7a=2(-10)........................................answer is 20/7

3a^2 + 3a^2 = 6a^2 3a^2 - 3a^2 = 0 3a^2 x 3a^2 = 9a^4 3a^2 divided by 3a^2 = 1

3 times3 times 2 times 2

22